Self consistent study of the quantum phases in a frustrated antiferromagnet on the bilayer honeycomb lattice - Arlego, Marcelo José Fabián (2014)
We study the frustrated Heisenberg model on the bilayer honeycomb lattice. The ground-state energy and spin gap are calculated, using different bosonic representations at mean field level and numerical calculations, to explore different sectors of the phase diagram. In particular we make use of a bond operator formalism and series expansion calculations to study the extent of dimer inter-layer phase. On the other hand we use the Schwinger boson method and exact diagonalization on small systems to analyze the evolution of on-layer phases. In this case we specifically observe a phase that presents a spin gap and short range Neel correlations that survives even in the presence of non-zero next-nearest-neighbor interaction and inter-layer coupling.